DEVELOPMENT AND VALIDATION OF LC-MS/MS METHOD FOR THE ESTIMATION OF ACRIVASTINE IN PHARMACEUTICAL DOSAGE FORM . - B, SNEHALATHA; D, GOWRI SANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â The objective of this study was to validate a simple, specific, accurate and precise solid phase high performance liquid chromatographic method with tandem mass spectrometry method for the determination of acrivastine (AC) in human plasma using pirfenidone as internal standard (ISTD). The precision and accuracy data have to fulfill the requirements for quantification of the analytes in biological matrices to generate data for bioequivalence and bioavailability investigations. A peerless basic C18, 5 Î¼ column having 4.6 mmÃ—100 mm internal diameter in binary gradient mode with flow rate was 0.8 mL/minutes of mobile phase containing methanol and 2 mm ammonium formate were used. The chromatographic separation was achieved by using elution solution consisting of methanol and 2 mm ammonium formate (70:30%, v/v)], diluent solution of methanol and water (50:50%, v/v)] were monitored on a triple quadrupole mass spectrometer, operating in the multiple reaction monitoring mode. The method was validated over the concentration range 0.5-205.170 ng/mL. Limit of detection and limit of quantification were found 0.18 ng and 0.536 ng, respectively. The retention time for AC and ISTD were 2 minutes and 2.4 minutes respectively and overall chromatography run time was 3.2 minutes. The mean recovery of AC (100.0%) and ISTD (102.5%) from spiked plasma samples was consistent and reproducible. The method was validated for linearity, accuracy, precision, specificity, limit of detection, limit of quantification and robustness. The intra- and inter-day precision and accuracy values were found to be within the assay variability limits as per the food and drug administration guidelines. Keywords: Acrivastine, Pirfenidone, Liquid chromatography tandem mass spectrometer, Linearity, Validation.Â